2011
DOI: 10.1159/000332397
|View full text |Cite
|
Sign up to set email alerts
|

Immunoadsorption Therapy for Steroid-Unresponsive Relapses in Patients with Multiple Sclerosis

Abstract: Background: Therapeutic plasma exchange (TPE) in steroid-unresponsive relapses of patients with multiple sclerosis (MS) is an established therapy with response rates of up to 70%. Immunoadsorption (IA) specifically removes immunoglobulins from the patient’s plasma. It is hypothesized that IA therapy might be better tolerated than and as effective as TPE in the treatment of MS relapses. Experiences with IA therapy of steroid-unresponsive MS relapses are limited. Methods: We report our experiences with IA therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0
11

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 25 publications
6
36
0
11
Order By: Relevance
“…We observed functional improvement in 71.4% of patients shortly after the IA series. Best response was observed in patients with ON with 84% improving in VA. Our results considerably increase evidence on the use of tryptophan IA as therapy for MS relapse and confirm previously published data [13,14,[16][17][18]21] . Studies on PE as escalating regimen for MS relapse predominantly included small patient numbers.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed functional improvement in 71.4% of patients shortly after the IA series. Best response was observed in patients with ON with 84% improving in VA. Our results considerably increase evidence on the use of tryptophan IA as therapy for MS relapse and confirm previously published data [13,14,[16][17][18]21] . Studies on PE as escalating regimen for MS relapse predominantly included small patient numbers.…”
Section: Discussionsupporting
confidence: 91%
“…In patients with optic neuritis (ON), the best corrected VA was used to monitor the clinical course. Changes in EDSS and VA were assessed by the following composite parameters for the definition of IA response similar to previous studies [9,12,16,20 ] . Moderate improvement represented a definite change of the neurologic deficit (decrease in EDSS by 0.5 steps in patients with initial EDSS 1-3.5 or improvement in VA ≥ 10 and <20%).…”
Section: Methods and Outcome Measuresmentioning
confidence: 99%
“…Two randomized sham-controlled studies have shown a beneficial effect of plasma exchange (PE) in adult patients with acute CNS demyelinating diseases failing to respond to treatment with ACTH or high-dose corticosteroids, respectively [2,3]. Additionally, one uncontrolled prospective study [4] and several case series [5,6] have shown comparable effects of immunoadsorption (IA) in such cases. The International Pediatric Multiple Sclerosis (MS) Study Group states: ‘Children with severe relapses not improving after high-dose IVMP pulse or with contraindications to glucocorticosteroids might benefit from a treatment with plasma exchange' [7].…”
Section: Introductionmentioning
confidence: 99%
“…In some countries, immunoadsorption (IA), a method to remove immunoglobulins from the circulation by adsorption to either tryptophan or protein A, is used as an alternative to TPE for the treatment of exacerbations of MS and NMOSD [46,47]. Several adult and pediatric cases have been reported in whom NMOSD attacks were successfully treated with IA [33,46,[48][49][50].…”
Section: Treatment Of Nmosd Attacksmentioning
confidence: 99%
“…Several adult and pediatric cases have been reported in whom NMOSD attacks were successfully treated with IA [33,46,[48][49][50].…”
Section: Treatment Of Nmosd Attacksmentioning
confidence: 99%